A combined experimental and theoretical study of photodouble ionization of water at 32 eV excess energy and unequal energy sharing. (17th February 2021) - Bolognesi, P; Randazzo, J M; Turri, G; Mathis, J; Penson, C; Ancarani, L U; Avaldi, L
Abstract: The photodouble ionization of water at about 32 eV excess energy has been investigated both experimentally and theoretically. In an energy and angular resolved photoelectron–photoelectron coincidence experiment, the two photoelectrons in unequal energy sharing (25 and 7 eV) condition, have been detected in a plane perpendicular to the propagation direction of the linearly polarized radiation. The measured angular distributions have been compared with, molecular orientation averaged, triple differential cross sections calculated with a recently developed theoretical model (Randazzo et al 2020 Phys. Rev. A 101 033407). The model uses separable products of orbitals as initial electronic state of the water molecule taken as a two-electron target and describes accurately the correlated two electron continuum. The combination of calculated cross sections corresponding to different dication states capture most of the measured features in terms of the evolution of both the shape and the intensity as a function of the faster electron direction which is set at 0°, 30° and 60° with respect to the polarization vector ε ⃗ of the incident radiation. A detailed analysis in terms of the different dication states as well as of the partial wave contributions to the electron pair wave function sheds light on the origin of such features.